GAMBARAN FUNGSI KOGNITIF PADA LANSIA DENGAN PEMBERIAN TERAPI PUZZLE - Nur Isnaini; Nabila Karimah Komsin (HUMAN CARE JOURNAL, 2020)
Description Of Cognitive Function In Elderly By Puzzle Therapy  Abstract Decreased cognitive function in the elderly will affect their daily activities and make them depend on others. The solution to overcome the problems is improving the elderly cognitive function. Puzzle Therapy  is a non-pharmacological therapy used to prevent cognitive decline. This research aimed to discover the Description Of Cognitive Function In Elderly By Puzzle Therapy  .This was Quasy Experimental research with a Pre and Posttest with Control Group approach. There were 36 elderly taken as the research sample using a total sampling technique. The research instrument used was MMSE. Data obtained were analyzed using Mann Whitney. The results showed of majority of the respondents were women. The average age of respondents was in the range of 60-74 years. Most of them did not go to school or only graduated from primary school.. Based on the Mann Whitney test result, the Asymp.Sig value was 0,000 (P value 0.05) there was an effect of Puzzle Therapy on the cognitive function of the elderly in Sudagaran Old Age Home, Banyumas. While based on the Shapiro-Wilk test, the p value was 0.05. Keywords: Puzzle Therapy; elderly; cognitive function.